EXTENT OF EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) INTEGRATION IN MALAYSIAN COMMUNITY COLLEGES - Peter, Crystal Joan; Libunao, Wilfredo Herrera; Abdul Latif, Adibah (Journal of Technical Education and Training, 2016)
This study was conducted to assess the extent to which ESD is being integrated in community colleges in Malaysia. It was pursued using quantitative-qualitative cross-sectional research design. The Sustainability Assessment Questionnaire (SAQ) developed by University Leaders for a Sustainable Future (ULSF) was modified and used as research instrument. Seven dimensions of sustainability in higher education institutions were covered in the SAQ (Curriculum; Research & Scholarship; Operation; Faculty and Staff Hiring, Development and Rewards; Outreach & Service; Student Opportunities; and Institutional Mission, Structure and Planning). Five community colleges, which were purposely selected based on the maturity level of the organization, and the number and type of programs being offered, were included in this study. Quantitative data was analysed using descriptive statistics with the aid of SPSS software version 16.0. The qualitative data was analysed using thematic content analysis. Results indicated that, to a certain extent, SD is integrated in all the seven dimensions of sustainability. The efforts however are still far from ideal indicating these institutions’ level of commitment to ESD. It is important for the community colleges to provide sustainability related courses/training programs as a way to increase sustainability awareness among its staff and students. Lecturers also should take their own initiatives and try to embed sustainability concepts in their research, teaching and learning activities in both formal and informal curriculum. A follow-up study needs to be pursued to cover more community colleges and determine the influence of leadership on successful ESD integration in all seven HEI dimensions.